The Level of Statistics Critical Thinking Skills among Institute of Teacher Education in Malay Language Campus Students - Mohd Afifi Baharudin Setambah; Norfadhilah Nasrudin; Roslina Suratnu; Haslinda Mohammad Saad; Sharizan Abdul Hamid (Institut Agama Islam Negeri Purwokerto, 2019)
The purpose of this article was to explore the level of critical thinking and differences in critical thinking skills between student based on gender and their class. This study uses survey design and implemented on 103 students. The objectives of the study can be achieved through the use of an evaluation instrument related to critical thinking skills in the context of statistics. Objective results showed no significant difference in gender. There was no significant difference between all class. Overall this study provides the Institute of Teacher Education in Malay Language Campus a better understanding of the level of critical thinking skills for their Preparatory Program for Bachelor of Teaching students. There also have to take action about this skill and where these skills are being taught within the curriculum.